Psychology of Nostalgia in Branding: A Literature Review - Fajar Santoso; Artha, Bhenu (Indo Publishing, 2025)
Nostalgia, a sentimental longing for the past, has emerged as a powerful psychological construct that shapes consumer attitudes, identity, and brand relationships across diverse market contexts. In branding, nostalgia can enhance affect, strengthen self-continuity, and foster social connectedness, which in turn elevate brand attachment, trust, and purchase intention. Strategically, firms deploy retro branding and heritage cues to evoke autobiographical and historical nostalgia, leveraging design, storytelling, and multisensory triggers to differentiate and create emotional resonance. However, effects are contingent on cohort relevance, authenticity, cultural context, and ethical practice, requiring careful measurement and design to avoid manipulation or exclusion. This review synthesizes foundational theories, mechanisms, executions, boundary conditions, methods, and future directions to guide evidence-based application of nostalgia in branding.